udyStudyStudyStudyStudy of of the Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extractthe Efficiency of Extract - Khalaf AL- Fatlawy , Yaaroub Faleh; Rasheed Majeed , Majid; Mohamed Dhedan , Basheer (Iraqi Journal of Science, 2023)
The aim of current study is estimate the ability of low cost adsorbents, which consist of extracted silica from rice husk ash in treatment of Industrial waste water that contains heavy metals (Cd, Co and Pb) with other pollutants by fixed filters technique with determine the best method for that, and study the effect of a number of variables and parameters. This study involved one waste water samples were collected from. State battery manufacturing company (SBMC) (before treatment unit) at 5th and 22th, of the January 2015. Adsorption tests showed that all tested adsorbent materials had a significant heavy metal removal efficiency. pH values showed a significant impact on adsorption process, but best removal efficiency occurred at pH 4.5 and 6 with removal efficiency for Cd 91% at pH 6, 90.8% at pH 4.5 respectively .Furthermore, the best pH for pb removal was ranged from 4 to 6, 77.75% to 71% and finally the pH of Co ranged from 4.5 to 6, 64.4% according to adsorbent materials and type of heavy metals in this study. Regarding contact time, adsorbent silica gel showed high adsorption efficiency at a variable time from 6 min to 93 min. for Cd, Co and pb. chemical and physical measurement were done for samples of industrial waste water before treatment and also after treating by adsorbents such as Cd, Co, Pb, pH, TDS, S, COD and EC. Moreover, the current work has examined the impact of various environmental variables such as pH values and contact time.